Modulation of gene expression in Kaposi's sarcoma-associated herpesvirus-infected lymphoid and epithelial cells. (September 2016) - Matteoli, Barbara; Broccolo, Francesco; Oggioni, Massimo; Scaccino, Antonio; Formica, Francesco; Ciccarese, Giulia; Drago, Francesco; Fusetti, Lisa; Esposito, Susanna; Ceccherini-Nelli, Luca
Aim: To evaluate the gene expression changes that occur soon after the active infection of two susceptible cell types with human herpesvirus 8 (HHV-8).Materials & methods: The expression profile of 282 human genes involved in the inflammatory process was investigated in HHV-8 A1 or C3 subtype-infected and mock-infected human epithelial cells and lymphoid cells.Results: The HHV-8-induced transcriptional profiles in the epithelial and lymphoid cells were very different. A robust increase in the expression was found in genes belonging to different categories, especially the categories of inflammation response and signal transduction.Conclusion: These results indicate that during early infection, HHV-8 induces a variety of cell type-specific processes, thus providing infection signatures useful as potential targets for therapeutic intervention.